Efeito do treinamento auditivo nas habilidades auditivas de crianças com transtorno do desenvolvimento da fala e da linguagem - Peters, Mariana Augusta Camasmie [UNIFESP] (2018)
Objective: To verify the effect of auditory training on the abilities of sound localization, auditory closure, figure-background, temporal ordering and temporal resolution of children with Phonological Disorder and Developmental Language Disorder and compare it to the effect of isolated language therapy. Methods: Six subjects, aged 5 to 7 years old at the beginning of the study, were selected: 2 girls and 4 boys; 3 with diagnosis of Developmental Language Disorder and 3 with Phonological Disorder. The subjects were submitted to behavioral auditory processing tests and, initially, to a 10 sessions individual intervention period only with speech therapy for developmental speech and language disorders, then, each subject was submitted to an intervention with conventional speech therapy combined with auditory training for a further 10 sessions period. Among the differentiated interventions, new evaluations were carried out with the same behavioral tests used in the initial evaluation. Results: After the combined therapy, there was an improvement in the hearing abilities of auditory closure, figure-background, temporal ordering and temporal resolution and all individuals presented evolution with gain in their auditory closure ability. The only auditory ability evaluated that did not show improvement with gain after the combined therapy was the sound localization. Conclusion: Conventional speech therapy combined with auditory training improves temporal processing and selective attention, with a better evolution in the auditory closure ability.